Wayang-based muhadatsah learning design in inclusive arabic language education from an islamic educational psychology perspective - Laili Mas Ulliyah Hasan; Siti Durotun Naseha; Saiul Anah; Dewi Sholeha Maisaroh (At Turots: Jurnal Pendidikan Islam, 2025)
Inclusive Arabic language learning requires instructional designs that accommodate students’ diverse cognitive, emotional, and learning characteristics, particularly those with special educational needs. Muhadatsah, as the core skill in Arabic speaking competence, often poses challenges for inclusive learners due to anxiety, low memory retention, limited exposure, and reduced verbal confidence. This study aims to design and analyze the implementation of the Wayang Puppet Theater as an innovative Muhadatsah learning medium rooted in Islamic educational psychology, emphasizing holistic development, positive emotion, and spiritual-humanistic learning values. Using a qualitative descriptive method, data were collected through classroom observations, reflective evaluations, and interviews with teachers and students in inclusive secondary schools. The learning design was developed based on William Francis Mackey’s theory of language learning and the principles of Islamic educational psychology related to motivation, emotional regulation, and affective learning behavior. The results indicate that Wayang-based Muhadatsah learning enhances students’ verbal participation, reduces speaking anxiety, encourages storytelling interaction, and supports cooperative communication. Students with special needs exhibited greater focus, emotional stability, and expressive responses compared to conventional textbook-based instruction. Teachers also noted that Wayang media simplifies lesson delivery, strengthens contextual understanding, and maintains classroom engagement without cognitive overload. This study concludes that the Wayang-based Muhadatsah design is pedagogically effective and culturally relevant for inclusive Arabic language education. Theoretically, it integrates Islamic educational psychology with culturally embedded media, while practically offering a feasible model for adaptive and inclusive learning environments. Future research is recommended to expand this model into digital-based applications to improve accessibility, sustainability, and broader implementation across Islamic educational institutions.